Hand hygiene in high-complexity sectors as an integrating element in the combat of Sars-CoV-2 - Danielle Galdino de Paula; Marianna Ramos Francisco; Juliana Dias Freitas; Renata Christine Quintella Levachof; Bianca de Oliveira Fonseca; Bruno Francisco Teixeira Simões; Rafael de Lima Bilio (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to perform a situational diagnosis of the behavior of health professionals concerning hand hygiene practices in highly-complex sectors. Methods: this quantitative and retrospective study was based on reports (2016 and 2017) of Adult and Pediatric ICUs of a Federal hospital in Rio de Janeiro. Results: one thousand two hundred fifty-eight opportunities for hand hygiene were analysed. The chance of professionals sanitizing hands in Pediatric ICUs is 41.61% higher than in Adult ICUs. Concerning proper hand hygiene, the medical team had a 39.44% lower chance than the nursing team. Others had a 30.62% lower chance when compared to the nursing team. The moment "after contact with the patient" presented 4.5275 times the chance in relation "before contact with the patient". Conclusion: in front of hand hygiene recommendations to control COVID-19, diagnostic assessment and previous analysis of the behavior of professionals proved to be positive.